Extrapolar climate reversal during the last deglaciation - Asmerom, Yemane (Sci Rep, 2017)
Large ocean-atmosphere and hydroclimate changes occurred during the last deglaciation, although the interplay between these changes remains ambiguous. Here, we present a speleothem-based high resolution record of Northern Hemisphere atmospheric temperature driven polar jet variability, which matches the Greenland ice core records for the most of the last glacial period, except during the last deglaciation. Our data, combined with data from across the globe, show a dramatic climate reversal during the last deglaciation, which we refer to as the Extrapolar Climate Reversal (ECR). This is the most prominent feature in most tropical and subtropical hydroclimate proxies. The initiation of the ECR coincides with the rapid rise in CO(2), in part attributed to upwelling in the Southern Ocean and the near collapse of the Atlantic Meridional Overturning Circulation. We attribute the ECR to upwelling of cold deep waters from the Southern Ocean. This is supported by a variety of proxies showing the incursion of deep Southern Ocean waters into the tropics and subtropics. Regional climate variability across the extropolar regions during the interval previously referred to as the “Mystery Interval” can now be explained in the context of the ECR event.